Spain : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Spain. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2020)
COVID-19 impact. The pandemic has hit Spain's society and economy severely following five years of strong job-rich growth. A large service sector dominated by SMEs, importance of tourism, and widespread use of temporary employment make the economy particularly vulnerable to the health crisis. It will take several years for the economy to recover, and the outlook is subject to strong downside risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet